Плиз...Упростите выражение: а) a+b\2ab:a+b\8a2b2 б) (4a^4b^3):(2a^3b\a+b)^3 в) 5a-x\5a+x*(5a+x)^2 г) 18m^2n^3\7pq*14p^2q\27m^3n^2

1

Ответы и объяснения

2013-08-06T12:00:40+04:00
а) a+b\2ab:a+b\8a2b2 = (a+b)*(8a^2b^2) / (2ab)*(a+b) = сокращаем = 4ab  
б) (4a^4b^3):(2a^3b\a+b)^3 = 
(4a^4b^3) : (8a^9b^3) / (a+b)^3 = (4a^4b^3) * (a+b)^3 / 8a^9b^3 = сокращаем = (a+b)^3 / 2a^5
в) 5a-x\5a+x*(5a+x)^2 = (5a-x) * (5a+x)^2 / 5a+x = сокращаем = (5a+x)(5a-x) = 25a^2-x^2
 г) 18m^2n^3\7pq*14p^2q\27m^3n^2 = (18m^2n^3)*(14p^2q) / (7pq)*(27m^3n^2) = сокращаем = 4np / 3m